Primary Breast Angiosarcoma: Serial Cases - Gunawan, Benny; Yohana Azhar; Monty P. Soemitro; Maman Abdurahman; Kiki A. Rizky; Bethy Hernowo (HM Publisher, 2024)
Background: Breast angiosarcoma is a rare malignancy arising from endothelial cell lining, approximately 0.04–0.05% of all breast malignancies and less than 1% of all sarcomas. Consisting of primary breast angiosarcoma (PAS) and secondary breast angiosarcoma (SAS). Diagnosis is often delayed because the case is rare and asymptomatic, the lump is painless, grows quickly, progressive disease can develop distant metastasize, and the prognosis is reportedly poor. Case presentation: This case series presents two cases of primary breast angiosarcoma; the first patient is a patient who needs to obtain a diagnosis through physical examination, imaging, surgery, histopathology, and immunohistochemistry. The second patient is how to reconstruct the surgical defect using the Latissimus dorsi flap, and interestingly, with thirteen years of survival without recurrence, Surgery is the main treatment with high local recurrence. Wide excision in the form of a simple mastectomy is recommended if a tumor-free margin of 2-3 cm cannot be achieved. Tumor excision, or cosmesis, is not achieved, which is related to the proportion of breast and tumor size. The use of radiation therapy and neoadjuvant or adjuvant chemotherapy is still controversial. Conclusion: Establishing a diagnosis with a thorough examination starts with anamnesis, physical examination, radiological examination, and histopathology, including immunohistochemistry, which is an important examination in confirming the diagnosis.